A framework and comparative analysis of web-based climate change visualization tools. (April 2022) - Lumley, Sam; Sieber, Renee; Roth, Robert
Abstract: Interactive and web-based data visualizations are now widely adopted to make climate change information more accessible, actionable, and meaningful. Despite the rapid uptake of such climate visualization tools (CVTs), there is little research on the design considerations that underpin their efficacy in meeting needs for climate change science and communication. To address this gap, we present a framework and comparative analysis of 41 public facing CVTs, assessing their purpose, data content, visual representation, interactivity, and web technology. Our analysis reveals several trends, including a tendency to focus on meteorological datasets over climate impacts, the widespread use of interactive maps for displaying climate data and the growing use of interactive options to promote sharing of results and user configurations. We found that distinguishing CVTs as being either "exploratory" or "explanatory" in their goal was useful in characterizing their visual and interactive complexity. We archived the analysis framework and repository of 41 coded tools on GitHub (available at https://github.com/smlum/climate-vis ) to support further analysis and improve the capacity of CVTs to reduce climate change and its impacts. Graphical abstract: Highlights: Climate visualizations can be characterized by their purpose, data, visual representations, interactivity, and technologies. Most climate visualizations focus on meteorological impacts. Interactive climate visualizations are increasingly targeted at non-scientists. Interface complexity differs between exploratory and explanatory visualizations. Established design innovations are overlooked in many climate visualizations.